Genetic polymorphism of inosine-triphosphate-pyrophosphatase influences mercaptopurine metabolism and toxicity during treatment of acute lymphoblastic leukemia individualized for thiopurine-S-methyl-transferase status. - Stocco, Gabriele; Crews, Kristine R; Evans, William E (Expert Opin Drug Saf, 2010)
IMPORTANCE OF THE FIELD: Although genetic polymorphisms in the gene encoding human thiopurine methyltransferase (TPMT) are known to have a marked effect on mercaptopurine metabolism and toxicity, there are many patients with wild-type TPMT who develop toxicity. Furthermore, when mercaptopurine dosages are adjusted in patients who are heterozygous at the TPMT locus, there are still some patients who develop toxicity for reasons that are not fully understood. Therefore, we recently studied the effects of a common polymorphism in another gene encoding an enzyme involved in mercaptopurine metabolism (SNP rs1127354 in inosine-triphospate-pyrophosphatase, ITPA), showing that genetic polymorphism of ITPA is a significant determinant of mercaptopurine metabolism and of febrile neutropenia following combination chemotherapy of acute lymphoblastic leukemia (ALL) in which mercaptopurine doses are individualized based on TPMT genotype. AREA COVERED IN THIS REVIEW: In this review, we summarize the knowledge available about the effect and clinical relevance of TPMT and ITPA on mercaptopurine pharmacogenomics, with a particular focus on the use of this medication in pediatric patients with ALL. WHAT THE READER WILL GAIN: Reader will gain insights into: i) the effects of pharmacogenomic traits on mercaptopurine toxicity and efficacy for the treatment of ALL and ii) individualization strategies that can be used to mitigate toxicity without compromising efficacy in pediatric patients with ALL. TAKE HOME MESSAGE: Mercaptopurine dose can be adjusted on the basis of TPMT genotype to mitigate toxicity in pediatric patients with ALL. As treatment is individualized in this way for the most relevant genetic determinant of drug response (i.e., for mercaptopurine, TPMT), the importance of other genetic polymorphisms emerges (e.g., ITPA).
Keywords: 6-Mercaptopurine; Antineoplastic Combined Chemotherapy Protocols; Child; Humans; Individualized Medicine; Methyltransferases; Models, Biological; Neutropenia; Nucleotide Transport Proteins; Polymorphism, Genetic; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Pyrophosphatases